2021
DOI: 10.3389/fsufs.2021.709401
|View full text |Cite
|
Sign up to set email alerts
|

Agroecological Transitions: A Systematic Review of Research Approaches and Prospects for Participatory Action Methods

Abstract: There have been many calls for an agroecological transition to respond to food shocks and crises stemming from conventional food systems. Participatory action research and transformative epistemologies, where communities are research actors rather than objects, have been proposed as a way to enhance this transition. However, despite numerous case studies, there is presently no overview of how participatory approaches contribute to agroecological transitions. The present article therefore aims to understand the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 54 publications
1
17
0
4
Order By: Relevance
“…Indeed, identified some studies that we considered to be participatory in nature, which did not use the term 'participatory' at all. As we approached the final stages of our review, a global systematic review was published that explored the use of participatory methods in agroecology, and the extent to which participatory approaches contribute to agroecology transitions (Sachet et al 2021). The authors of this opted to limit the search results by including "case study" as a keyword.…”
Section: Types Of Participatory Research Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, identified some studies that we considered to be participatory in nature, which did not use the term 'participatory' at all. As we approached the final stages of our review, a global systematic review was published that explored the use of participatory methods in agroecology, and the extent to which participatory approaches contribute to agroecology transitions (Sachet et al 2021). The authors of this opted to limit the search results by including "case study" as a keyword.…”
Section: Types Of Participatory Research Methodsmentioning
confidence: 99%
“…Sachet et al also identified a diverse range of participatory methods, including participatory rural appraisal (PRA), rapid rural appraisal (RRA), participatory learning, and participatory action research. They described some participatory methods as 'extractive' meaning that "participants are consulted on a particular topic without opening space for co-learning, interaction, and potential selfmobilization" (Sachet et al 2021).…”
Section: Types Of Participatory Research Methodsmentioning
confidence: 99%
“…Such holistic approaches can provide support for decision-making by making use of these existing agricultural knowledge bases. Farmers innovate and experiment, their accumulated knowledge and expertise can provide valuable information about the practical implications and potential efficacy of agroecology interventions at the farm (Sachet et al 2021) and landscape level.…”
Section: Addressing System Complexitymentioning
confidence: 99%
“…Collaborative approaches to policy design can contribute to overcoming cognitive barriers to the adoption of agroecological practices by farmers and new approaches to the food system (as proposed in the ‘Partnership on Accelerating farming systems transition: agroecology living labs and research infrastructures’, European Commission, 2022). They have the potential to improve the results of agri‐environmental schemes by increasing the adoption of practices, fostering environmental synergies and, in turn, strengthening community and family networks (Sachet et al ., 2021). However, they can create barriers and discourage participation, leading to trade‐offs that must be addressed in policy design (Legras et al ., 2021).…”
Section: Partnerships Cooperation and Social Capitalmentioning
confidence: 99%
“…community and family networks (Sachet et al, 2021). However, they can create barriers and discourage participation, leading to trade-offs that must be addressed in policy design .…”
mentioning
confidence: 99%